Facial Reconstruction: A Systematic Review of Current Image Acquisition and Processing Techniques - Tarassoli, Sam P.; Shield, Matthew E.; Allen, Rhian S.; Jessop, Zita M.; Dobbs, Thomas D.; Whitaker, Iain S. (Frontiers in Surgery, 2020)
Introduction Plastic and reconstructive surgery is based on a culmination of technological advances, diverse techniques, creative adaptations and strategic planning. 3D imaging is a modality that encompasses several of these criteria while encouraging the others. Imaging techniques used in facial imaging come in many different modalities and sub-modalities which is imperative for such a complex area of the body; there is a clear clinical need for hyper-specialised practice. However, with this complexity comes variability and thus there will always be an element of bias in the choices made for imaging techniques. Aims and Objectives The aim of this review is to systematically analyse the imaging techniques used in facial reconstruction and produce a comprehensive summary and comparison of imaging techniques currently available, including both traditional and novel methods. Methods The systematic search was performed on EMBASE, PubMed, Scopus, Web of Science and Cochrane reviews using keywords such as ‘image technique/acquisition/processing’, ‘3-Dimensional’, ‘Facial’ and ‘Reconstruction’. The PRISMA guidelines were used to carry out the systematic review. Studies were then subsequently collected and collated; followed by a screening and exclusion process with a final full-text review for further clarification in regard to the selection criteria. A risk of bias assessment was also carried out on each study systematically using the respective tool in relation to the study in question. Results From the initial 6147 studies, 75 were deemed to fulfil all selection criteria and selected for meta-analysis. The majority of papers involved the use of computer tomography, though the use of magnetic resonance and handheld scanners using sonography have become more common in the field. The studies ranged in patient population, clinical indication. Seminal papers were highlighted within the group of papers for further analysis. Conclusions There are clearly many factors that affect the choice of image acquisition techniques and their potential at being ideal for a given role. Ultimately the surgical team’s choice will guide much of the decision, but it is crucial to be aware of not just the diagnostic ability of such modalities, but their treatment possibilities as well.